2008
DOI: 10.1093/humrep/den060
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of antioxidant supplementation in sperm-preparation medium against oxidative stress in human spermatozoa

Abstract: Supplementing sperm preparation medium with EDTA or catalase significantly improved the overall functional parameters of the spermatozoa by reducing the ROS levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 33 publications
1
65
0
4
Order By: Relevance
“…[93][94][95][96] In contrast, other studies have reported that antioxidants (e.g., glutathione and catalase) are ineffective in protecting spermatozoa from the loss of motility during sperm processing. [97][98][99] It is important to note that sperm samples from infertile men may be more susceptible to oxidative injury (from semen processing) and be afforded greater protection by antioxidants than samples from fertile men. 92 Antioxidants appear to be of limited value in protecting sperm DNA from gentle semen processing (e.g., incubation or densitygradient centrifugation) ( Table 5).…”
Section: Role Of In Vitro Antioxidants In Protecting Spermatozoa Frommentioning
confidence: 99%
See 1 more Smart Citation
“…[93][94][95][96] In contrast, other studies have reported that antioxidants (e.g., glutathione and catalase) are ineffective in protecting spermatozoa from the loss of motility during sperm processing. [97][98][99] It is important to note that sperm samples from infertile men may be more susceptible to oxidative injury (from semen processing) and be afforded greater protection by antioxidants than samples from fertile men. 92 Antioxidants appear to be of limited value in protecting sperm DNA from gentle semen processing (e.g., incubation or densitygradient centrifugation) ( Table 5).…”
Section: Role Of In Vitro Antioxidants In Protecting Spermatozoa Frommentioning
confidence: 99%
“…92 Antioxidants appear to be of limited value in protecting sperm DNA from gentle semen processing (e.g., incubation or densitygradient centrifugation) ( Table 5). [98][99][100][101] In some cases, antioxidants supplementation in vitro (e.g., combination of vitamins C and E) may cause sperm DNA damage. 99,101 ROLE OF IN VITRO ANTIOXIDANTS IN PROTECTING SPERMATOZOA FROM CRYOPRESERVATION AND THAWING Several studies have evaluated the role of antioxidants in protecting spermatozoa from the loss of motility that occurs following cryopreservation and thawing.…”
Section: Role Of In Vitro Antioxidants In Protecting Spermatozoa Frommentioning
confidence: 99%
“…In general, antioxidants appear to be of limited value in protecting sperm DNA from gentle semen processing (e.g. incubation or density-gradient centrifugation) (see Table 4) [62][63][64][65]. In some cases, antioxidants supplementation in vitro (e.g.…”
Section: In Vitro Antioxidants and Sperm Dna Damagementioning
confidence: 99%
“…Superoxide dismutase and catalase were shown to improve sperm survival, reduce ROS generation in boar spermatozoa and prevent human sperm membrane lipid peroxidation during freeze-thaw procedures [12,13]. Catalase had pronounced effects on improving the post-thaw quality of canine spermatozoa and the overall functional parameters of human spermatozoa [14,15]. Glutathione peroxidase activity was shown to be important against lipid peroxidation in human spermatozoa because lipid peroxidation increased significantly either through the inhibition of glutathione peroxidase action or by depleting glutathione availability [16].…”
Section: Introductionmentioning
confidence: 99%